2020
DOI: 10.3390/ijerph17093057
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating an Educational Program for Respiratory Infection Prevention among Rural Elderly Residents in South Korea

Abstract: Based on social cognitive theory (SCT), an educational program was developed to prevent rural elderly residents from respiratory infections in South Korea. The effectiveness of the program was investigated in terms of knowledge, attitudes, and practices about respiratory infection prevention, as well as social capital. A pretest–posttest nonequivalent control group quasi-experimental design was used to test the short-term effect of this program. In addition, 1- and 6-month follow-up surveys were administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…According to our PICOS criteria, the participants were designated as the adults over 18 years of age. In detail, the age of the subject in the study of Barrett et al [ 10 ] was specifically 30–69 years old, and the study conducted by Kim et al [ 6 ] also reported subjects’ age as over 60 years old. However, there age of the subjects in the other studies was not accurately specified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our PICOS criteria, the participants were designated as the adults over 18 years of age. In detail, the age of the subject in the study of Barrett et al [ 10 ] was specifically 30–69 years old, and the study conducted by Kim et al [ 6 ] also reported subjects’ age as over 60 years old. However, there age of the subjects in the other studies was not accurately specified.…”
Section: Resultsmentioning
confidence: 99%
“…The countries in which the study was conducted were: US [ 10 ], four in Europe (United Kingdom [ 4 ], Germany [ 9 ], Finland [ 5 ], Netherlands [ 2 ]), four in Asia (Malaysia [ 3 ], Thailand [ 8 ], two for the Republic of Korea [ 6 , 7 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations